Basuki Rahmat Corridor’s sidewalk: an observation - Veronica Mandasari (Institute for Advanced Science Social, and Sustainable Future, 2023)
The Tunjungan area, especially the Jalan Basuki Rahmat corridor, is the object of this study because this corridor is an essential element of accessibility for the trade and service area of Surabaya City.. This study aims to observe the environment of the Basuki Rahmat Street corridor and identify the condition of the existing pedestrian paths. The research questions are as follows: (1) Identifying Basuki Rahmat corridor in general; (2) Analysing sidewalk’s condition along the Basuki rahmat corridor. This research has clear goals because the previous research has yet to elaborate detailed information on the Basuki Rahmat corridor comprehensively. Thus, this study will produce profound observations on how the sidewalk condition is maintained and affects surrounding land use. Observations were made by visiting the study location directly to observe the existing condition of the pedestrian paths in the Jalan Basuki Rahmat Corridor, Surabaya. Observations were carried out in 3 ways, namely (1) field observations related to the existence of facilities, furniture, and the condition of the pedestrian paths, and (2) direct measurements related to the dimensions of the pedestrian paths. From the study, the researcher found that 92,4% of the land uses are covered by commercial areas. Meanwhile, 2084,43 meters (0,2 km) of the pedestrian paths is Sidewalk, and 197 meters (0,01 km) is Arcade. Another important point to note is the social interaction that occurs is due to the existence of a motorcycle community that utilizes pedestrian paths on weekends. Overall, the researcher discovered that Basuki Rahmat Corridor has an enormous potential to be a walkable area if the facilities are improved. The land use environment has already given a lively vibe because of the various activities offered, yet the stakeholders still need to be concerned with the sustainability of the corridor.